2023
DOI: 10.1021/acsami.3c00554
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate Additives Improve the Low-Temperature Performance of LiNi0.8Mn0.1Co0.1O2||SiOx@Graphite Lithium-Ion Batteries

Abstract: LiNi0.8Mn0.1Co0.1O2||SiOx@graphite (NCM811||SiOx@G)-based lithium-ion batteries (LIBs) exhibit high energy density and have found wide applications in various fields, including electric vehicles. Nonetheless, its low-temperature performance remains a challenge. One of the most efficacious strategies to enhance the low-temperature functionality of battery is the development of appropriate electrolytes with low-temperature suitability. Herein, p-tolyl isocyanate (PTI) and 4-fluorophenyl isocyanate (4-FI) are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(109 reference statements)
1
1
0
Order By: Relevance
“…In comparison, LiN x O y originating from the decomposition of LiNO 3 is detected in the +10% FEC + 0.5 M LiNO 3 electrolyte (Figure d). The above results demonstrate that the joint addition of FEC and LiNO 3 contributes to the formation of intact SEI, in which the combination of LiF and LiN x O y enables good mechanical properties and fast ion conductivity . The XPS analyses are in accordance with the coordination structures.…”
Section: Resultssupporting
confidence: 60%
“…In comparison, LiN x O y originating from the decomposition of LiNO 3 is detected in the +10% FEC + 0.5 M LiNO 3 electrolyte (Figure d). The above results demonstrate that the joint addition of FEC and LiNO 3 contributes to the formation of intact SEI, in which the combination of LiF and LiN x O y enables good mechanical properties and fast ion conductivity . The XPS analyses are in accordance with the coordination structures.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, we have observed that the presence of the electrolyte significantly reduces the thermal stability of both the positive and negative electrodes, lowering the temperature of heat generation and increasing the amount of heat released. Therefore, from the perspective of battery design, developing safer and more stable electrolytes (Han et al, 2023) or using solid-state electrolytes (J. Wang et al, 2023) are also important measures to prevent accidents.In summary, the exothermic reaction associated with the negative electrode exhibits significant heat generation over a long period, while the reaction associated with the positive electrode Experimental phenomena and temperature-voltage curve of cell heating test.…”
Section: Trigger Heat Production Characteristics Of Cellmentioning
confidence: 99%
“…With standard EC-based electrolytes, NMC||SiO x -Gr cells cannot reach their full potential, especially under extreme conditions such as high-rate charging or low temperature operation. [24][25][26][27] The standard EC-based electrolytes exhibit low ionic conductivity and high viscosity, and they have a high desolvation energy barrier for lithium ions. 28,29 Consequently, during charging under extreme conditions, lithium ions tend to deposit on the anode surface rather than intercalating into the graphite or alloying with silicon.…”
mentioning
confidence: 99%